The Role of Community Traditional Institutions in Dispute Resolution in Multicultural Communities - Habib Fuqoha; Gina Anggita Putri; Aldi Alfarizi; Sigit Gunawan; Diky Dikrurahman (Journal of World Science, 2024)
Indonesian society is pluralistic, consisting of various ethnic groups, religions, and customs. This diversity can trigger various disputes in multicultural societies. This research aims to analyze the role of societal institutions in dispute-resolution efforts in multicultural communities. This study uses a qualitative research method with a literature study approach, focusing on societal institutions as the primary subjects, specifically their role and effectiveness in managing disputes. Data from various sources were analyzed in three stages: data reduction, presentation, and conclusion drawing. The research results show that society institutions play a significant role in resolving disputes through mechanisms such as deliberation for consensus, customs, and customary sanctions. Strengthening the role of these institutions is essential for maintaining social harmony by increasing community understanding of customary law and building synergy between customary institutions and state law.